Estudo e aplicação de uma estratégia de controle ótimo na dinâmica populacional do Aedes - Apergis, Lucas Gasperini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Diseases as Dengue, Zika and Chikungunya are directly related to the mosquito vector Aedes aegypti, taking into consideration its high capacity in disease spreading, mainly in tropical regions. The mathematical modeling of its populational dynamic is extremely important to elucidate the transmission mechanisms of these diseases. The objective of this work was the study of the optimal mechanical control over the mosquito cycle of life in its aquatic phase. The optimization process was formulated through the Mayer Problem, derived from the Lagrange Problem, but with computational advantage. This study has also been extended to cover the SIR modeling (Susceptible-Infected-Recovered), considering the vacination of the susceptible class in order to reduce the number of infected. The model considering vaccination model was analyzed mathematically and computational simulations were made to illustrate the convergence of the numerical results to the equilibrium points. Comparisons between the results show the effectiveness of the optimal control in reducing the Aedes population and infected humans.

Doenças como a Dengue, a Zika e a Chikungunya estão diretamente ligadas ao mosquito transmissor Aedes aegypti, levando em consideração sua ampla capacidade de disseminação de doenças, principalmente em regiões tropicais. A modelagem matemática da dinâmica populacional do Aedes é de extrema importância para elucidar os mecanismos de transmissão dessas doenças. O objetivo deste trabalho foi o estudo de um controle mecânico otimizado aplicado na dinâmica populacional do ciclo de vida do mosquito em sua fase aquática. O processo de otimização foi formulado por meio do Problema de Mayer, derivado do Problema de Lagrange, mas com vantagens computacionais. Este estudo também foi estendido na modelagem SIR (Susceptível-Infectado-Recuperado), considerando a vacinação da classe dos indivíduos susceptíveis, com o intuito de reduzir o número de infectados. O modelo com vacinação foi analisado matematicamente e simulações computacionais foram realizadas para ilustrar a convergência dos resultados numéricos para os pontos de equilíbrio. Comparações dos resultados mostram a eficiência do controle otimizado na redução da população do Aedes e dos humanos infectados.
Study and appplication of an optimal control strategy over Aedes populational dynamic
Keywords: Mechanical control; Optimization; Computational population dynamics; Matemática; Arboviroses; Análise do ponto de equilíbrio; Dinâmica populacional; Otimização matemática; Aedes aegypti; Dengue